Wild-type and Brachyolmia-causing Mutant TRPV4 Channels Respond Directly to Stretch Force - Loukin, Stephen (American Society for Biochemistry and Molecular Biology, 2010)
Whether animal ion channels functioning as mechanosensors are directly activated by stretch force or indirectly by ligands produced by the stretch is a crucial question. TRPV4, a key molecular model, can be activated by hypotonicity, but the mechanism of activation is unclear. One model has this channel being activated by a downstream product of phospholipase A(2), relegating mechanosensitivity to the enzymes or their regulators. We expressed rat TRPV4 in Xenopus oocytes and repeatedly examined >200 excised patches bathed in a simple buffer. We found that TRPV4 can be activated by tens of mm Hg pipette suctions with open probability rising with suction even in the presence of relevant enzyme inhibitors. Mechanosensitivity of TRPV4 provides the simplest explanation of its various force-related physiological roles, one of which is in the sensing of weight load during bone development. Gain-of-function mutants cause heritable skeletal dysplasias in human. We therefore examined the brachyolmia-causing R616Q gain-of-function channel and found increased whole-cell current densities compared with wild-type channels. Single-channel analysis revealed that R616Q channels maintain mechanosensitivity but have greater constitutive activity and no change in unitary conductance or rectification.